2019
DOI: 10.3892/mmr.2019.9977
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorating effects of Cuscuta chinensis Lamak extract on hind‑limb ischemia, and angiogenic‑ or inflammatory associated factors in ovariectomized mice

Abstract: Cuscuta chinensis Lamak (CCL) has traditionally been used in Korea to treat sexual disorders and skin problems. The aim of the present study was to investigate the effects of CCL extract on surgical injury-induced ischemia in the hind limbs of mice. Specifically, female C57BL/6 mice were ovariectomized, and their hind-limb vessels were ligated with surgical silk (6-0) and excised. CCL (150 or 450 mg/kg/BW) was then administered to the mice for 3 weeks, and the blood flow rate was evaluated using a laser Dopple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…Notably, these results are consistent with those of a study conducted by Kang et al, 2014, which reported that C. chinensis extracts had the ability to suppress the production of TNF-α, IL-1β, and IL-6 by down regulating their transcription levels [12]. Kim et al, 2019, also reported that C. chinensis extracts reduced the transcriptional levels of inflammatory factors, including TNF-α, IL-6, and IL-1β, in mice [13]. Another study investigated the anti-inflammatory properties of a C. chinensis extract in mice when administered at concentrations of 100 and 500 mg/kg.…”
Section: The Effects Of C Chinensis Seed Extracts On Inhibiting Gene ...supporting
confidence: 92%
See 1 more Smart Citation
“…Notably, these results are consistent with those of a study conducted by Kang et al, 2014, which reported that C. chinensis extracts had the ability to suppress the production of TNF-α, IL-1β, and IL-6 by down regulating their transcription levels [12]. Kim et al, 2019, also reported that C. chinensis extracts reduced the transcriptional levels of inflammatory factors, including TNF-α, IL-6, and IL-1β, in mice [13]. Another study investigated the anti-inflammatory properties of a C. chinensis extract in mice when administered at concentrations of 100 and 500 mg/kg.…”
Section: The Effects Of C Chinensis Seed Extracts On Inhibiting Gene ...supporting
confidence: 92%
“…Moreover, it was found that C. chinensis seed extract could suppress the phosphorylation of extracellular-signal-regulated kinase 1/2, Jun N-terminal kinase, p38 mitogen-activated protein kinase, and NF-κB p65 in activated microglia [12]. Another study found that C. chinensis extract exhibited therapeutic potential for the treatment of hind-limb ischemia, as it promoted peripheral angiogenic and anti-inflammatory effects in mice [13].…”
Section: Introductionmentioning
confidence: 98%
“…injection with E2 and the COM extract (150 and 300 mg/kg/day) and then euthanized 12 hours after the final injection. The normal and positive controls of this study have already been described in previous studies 13 . All animal experiments were approved by the Ethics Committee of Korea Institute of Oriental Medicine (approved No.…”
Section: Methodsmentioning
confidence: 99%
“…Peripheral arterial diseases (PAD) are severe medical conditions, which are characterized by blood vascular blockage and low limb Doppler signals and commonly associated with hind-limb ischemia or critical limb ischemia (CLI) [103]. For decades, we and other investigators have primarily suggested the therapeutic of MSCs or MSCderived exosomes in hind limb ischemia models by alleviating the severity, promoting angiogenesis, and enhancing immunomodulation [9,104,105].…”
Section: Hydrogels/mscs Scaffolds For Vascular Diseasesmentioning
confidence: 99%